Using Multimedia Materials in the Teaching of Scientific and Technical Translation - Prieto Velasco, Juan Antonio; Tercedor Sánchez, Maribel; López Rodríguez, Clara Inés (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Information technology has changed the professional environment of scientific and technical translators, who must work with new formats and channels of information. To meet these new challenges, translation teachers must place special emphasis on the importance of the non-textual information evolving around multimedia texts and adopt a more dynamic approach towards audiovisual translation (A VT). In this paper, we argue for the inclusion of graphic information as a new focus for A VT, and present the results of a research project aimed at designing teaching materials for audiovisual, scientific and technical translation. These materials highlight the potential benefits of audiovisual resources for all users in the acquisition of subject field knowledge and terminology and the constraints imposed on translation by visual and acoustic material.